Burnout, compassion for others and fear of compassion: a quantitative study in Iranian nurses - Khanjani,Sajad (2021)
Abstract Introduction Occupational burnout in nurses is a barrier to job promotion and achievement of job-related goals, resulting in reduced hospital performance. Objective Considering the importance of the role of compassion in occupational burnout among nurses, this cross-sectional study aimed to explore the burnout levels and their relationships with compassion for others and fear of compassion. Methods This descriptive correlation study was carried out with 216 nurses who were selected using a multistage cluster sampling method and asked to respond to the Maslach Burnout Inventory, a compassion for others scale and Fears of Compassion Scales (FCS), which includes three subscales; fears of compassion for self, compassion for others, and compassion from others. Results The results showed that burnout had a negative correlation with compassion for others, but had positive correlations with fear of compassion for others, fear of compassion from others, and fear of self-compassion. Moreover, the results of regression analysis showed that 21% of burnout variance was explained by compassion for others and 29% of its variance was explained by fears of compassion scales. Conclusion Based on the findings, compassion can be considered as a protective factor in preventing burnout among nurses.